The secrets we bury - Ramey, Stacie (Naperville, Illinois : Sourcebooks Fire, 2018)
Rather than be placed in a special school for psychologically-challenged students, Dylan, six months from turning eighteen, sets out on the Appalachian Trail, where he makes surprising connections with other hikers.
Keywords: Hiking -- Fiction; Family problems -- Fiction; People with mental disabilities -- Fiction; Interpersonal relations -- Fiction; Grief -- Fiction; Appalachian Trail -- Fiction